Multi-Level 3D Implementation of Thermo-Pneumatic Pumping on Centrifugal Microfluidic CD Platforms - Thio, Tzer Hwai Gilbert; Ibrahim, Fatimah; Al-Faqheri, Wisam; Soin, Norhayati; Abdul Kahar, Maria Kahar Bador; Madou, Marc (IEEE, 2013)
Thermo-pneumatic (TP) pumping is a method employing the principle of expanding heated air to transfer fluids back towards the CD center on the centrifugal microfluidic CD platform. While the TP features are easy to fabricate as no moving parts are involved, it consumes extra real estate on the CD, and because heating is involved, it introduces unnecessary heating to the fluids on the CD. To overcome these limitations, we introduce a multi-level 3D approach and implement forced convection heating. In a multi-level 3D CD, the TP features are relocated to a separate top level, while the microfluidic process remains on a lower bottom level. This allows for heat shielding of the fluids in the microfluidic process level, and also improve usage of space on the CD. To aid in future implementations of TP pumping on a multi-level 3D CD, studies on the effect of heat source setting, and the effect of positioning the TP feature (it distance from the CD center) on CD surface heating are also presented. In this work, we successfully demonstrate a multi-level 3D approach to implement TP pumping on the microfluidic CD platform.